2015
DOI: 10.1088/0004-637x/813/1/77
|View full text |Cite
|
Sign up to set email alerts
|

The Scaling Relations and the Fundamental Plane for Radio Halos and Relics of Galaxy Clusters

Abstract: Diffuse radio emission in galaxy clusters is known to be related to cluster mass and cluster dynamical state. We collect the observed fluxes of radio halos, relics, and mini-halos for a sample of galaxy clusters from the literature, and calculate their radio powers. We then obtain the values of cluster mass or mass proxies from previous observations, and also obtain the various dynamical parameters of these galaxy clusters from optical and X-ray data. The radio powers of relics, halos, and mini-halos are corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 110 publications
(90 reference statements)
4
77
0
1
Order By: Relevance
“…It has been found that the radio power of halos correlate with the X-ray luminosity of the host cluster (Brunetti et al 2007Cassano et al 2013;Yuan et al 2015). In Fig.…”
Section: Halo Spectral Index Estimatementioning
confidence: 88%
“…It has been found that the radio power of halos correlate with the X-ray luminosity of the host cluster (Brunetti et al 2007Cassano et al 2013;Yuan et al 2015). In Fig.…”
Section: Halo Spectral Index Estimatementioning
confidence: 88%
“…For several relics, the jump in X-ray surface brightness and/or temperature maps has been clearly measured (e.g., Sarazin et al 2014;Akamatsu et al 2015;Botteon et al 2016;van Weeren et al 2016). In addition to the shocks found in several clusters, the disturbance of the cluster X-ray surface brightness, as measured by power ratios, centroid shifts and concentration parameters, shows that relics are, in general, related to ongoing mergers (Yuan et al 2015).…”
Section: Introductionmentioning
confidence: 95%
“…The MeerKLASS survey is expected to detect a radio halo and/or relic in approximately 200 clusters, lower in mass and over a broad range of redshift, greatly extending the current number of ∼ 65 sources [25]. This statistically significant sample of diffuse emission is crucial for advancing the understanding of its formation and evolution.…”
Section: Diffuse Cluster Emissionmentioning
confidence: 99%